2019
DOI: 10.3389/fpsyg.2019.00522
|View full text |Cite
|
Sign up to set email alerts
|

Fat-Free Mass and Bone Mineral Density of Young Soccer Players: Proposal of Equations Based on Anthropometric Variables

Abstract: Background The assessment of body composition may assist in optimizing competitive efficiency and monitoring the success of training regimes for young soccer players. The purpose of this study was to determine the predictors for Fat-Free Mass (FFM) and Bone Mineral Density (BMD) of young soccer players. Also, the goal was to propose regression equations to estimate FFM and BDM through anthropometric variables. Methods One hundred and sixty-seven young soccer players age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
2
8
0
3
Order By: Relevance
“…Additionally, a high fat mass percentage (%FM) negatively affects endurance, strength and power qualities, which are assessed by soccer-specific tests [8,10]. Indeed, recent studies have shown that advanced biological maturity, within single year chronological age (CA) categories, is associated with advantages in body size and fat free mass (FFM) in adolescent athletes [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a high fat mass percentage (%FM) negatively affects endurance, strength and power qualities, which are assessed by soccer-specific tests [8,10]. Indeed, recent studies have shown that advanced biological maturity, within single year chronological age (CA) categories, is associated with advantages in body size and fat free mass (FFM) in adolescent athletes [5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have previously evidenced these relationships in other sports modalities such as judo, karate, tennis, basketball, soccer. [26][27][28][29][30] There is now strong empirical evidence that physical exercise affects normal muscle and bone development, 31,32 specifically muscular resistance training is important to improve strength, increase lean mass (regional and body) and prevent risk factors that may compromise the mineral integrity of bone tissue, in any age group and of both sexes. 33 Young baseball players classified with low bone density and bone .…”
Section: Discussionmentioning
confidence: 99%
“…Las causas de estas diferencias están marcadas por la mayor actividad física que tienen que soportar los huesos de la pierna, ya que están continuamente soportando el cuerpo y las acciones del balón. Por otro lado, el estudio de Zouch et al (2008), el BMC podría deberse al nivel de desarrollo en el que se encuentran los niños, ya que la pubertad es la etapa en la que los niños experimentan una mayor curva de crecimiento (Gomez-Campos et al, 2019). Por otro lado, también se observó una disminución del porcentaje de masa grasa con el entrenamiento.…”
Section: Discussionunclassified